2016
DOI: 10.1371/journal.pone.0148199
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Real Time Navigation in the Region of the Posterior Pelvic Ring: An Experimental In-Vitro Feasibility Study and Comparison of Image Guided Techniques

Abstract: BackgroundElectromagnetic tracking is a relatively new technique that allows real time navigation in the absence of radiation. The aim of this study was to prove the feasibility of this technique for the treatment of posterior pelvic ring fractures and to compare the results with established image guided procedures.MethodsTests were performed in pelvic specimens (Sawbones®) with standardized sacral fractures (Type Denis I or II). A gel matrix simulated the operative approach and a cover was used to disable vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…As such, improving the accuracy of placement of the guide wires using the conventional method increases both intra-operative time and radiation exposure, which limits the use of this iterative approach for accurate guide wire placement in clinical practice. Different assistive tools have been used to improve the accuracy and efficiency in placing guide wires, including the use of multidimensional fluoroscopy [ 20 ], an internal template [ 8 , 9 ], thermoplastic membrane navigation [ 21 ], and computer-assisted navigation [ 5 , 6 , 17 , 22 ]. Our external template is distinctive from these assistive approaches, with greater pre-operative time taken to design and print the navigation template, which avoids the need for repeated fluoroscopy during the surgery and reduces the overall operative time.…”
Section: Discussionmentioning
confidence: 99%
“…As such, improving the accuracy of placement of the guide wires using the conventional method increases both intra-operative time and radiation exposure, which limits the use of this iterative approach for accurate guide wire placement in clinical practice. Different assistive tools have been used to improve the accuracy and efficiency in placing guide wires, including the use of multidimensional fluoroscopy [ 20 ], an internal template [ 8 , 9 ], thermoplastic membrane navigation [ 21 ], and computer-assisted navigation [ 5 , 6 , 17 , 22 ]. Our external template is distinctive from these assistive approaches, with greater pre-operative time taken to design and print the navigation template, which avoids the need for repeated fluoroscopy during the surgery and reduces the overall operative time.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, its safety and accuracy is always doubted by experienced Chinese doctors who are good at free-hand screw insertion, have great confidence in their ability to perform this technique, or just dislike complicated procedures. However, some high-level clinical studies [ 8 10 ] have reported that previous tools all have adequate safety and accuracy for spine surgery, such as conductivity measurement devices that detect cortical defects in the screw trajectory, and been improved [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Navigated fixation is currently regarded as a research tool and cannot yet be judged as a routine method [14].…”
Section: Current Surgical Techniquesmentioning
confidence: 99%